Sentence Writing Intervention for At‐Risk Writers in Upper Elementary Grades. Issue 4 (22nd September 2021) - Smith, R. Alex; Allen, Abigail A.; Panos, Kristin L.; Ciullo, Stephen
Abstract: Fluent production of a variety of grammatically correct sentences is essential to overall writing quality across genres. Sentence‐production skills become increasingly important as students prepare to transition from the elementary grades to middle‐school. Many students in the upper‐elementary grades, however, struggle with sentence production skills—especially writers with a learning disability. This paper provides useful information for educators focusing on improving the quality of sentence‐level writing skills for students with learning disabilities in Grades 3–5. Specifically, guidance is provided for using (a) assessment to inform sentence‐level intervention and (b) a sequence of instructional practices for improving foundational sentence‐level production skills.